2010
DOI: 10.1186/1744-9081-6-64
|View full text |Cite
|
Sign up to set email alerts
|

Central nitrergic system regulation of neuroendocrine secretion, fluid intake and blood pressure induced by angiotensin-II

Abstract: BackgroundNitric oxide (NO) synthesis has been described in several circumventricular and hypothalamic structures in the central nervous system that are implicated in mediating central angiotensin-II (ANG-II) actions during water deprivation and hypovolemia. Neuroendocrine and cardiovascular responses, drinking behavior, and urinary excretions were examined following central angiotensinergic stimulation in awake freely-moving rats pretreated with intracerebroventricular injections of Nω-nitro-L-arginine methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
(60 reference statements)
5
14
0
Order By: Relevance
“…In 2 additional animals where we acquired additional R 2 maps (data not shown), the data did suggest an increase in R 2 in IM after iodixanol; however, the magnitude of change was relatively small (approximately 10 s –1 ) compared with the observed R 2* change (approximately 100 s –1 ). Because it was also previously shown that L-NAME could reduce urine output, 41 it may explain why the R 2* was lower in the CIAKI-susceptible group after iodixanol. Although ioxalgate did show statistically significant increase in R 2* in IM, the values were comparable with the defined threshold (estimated slope of 0.32 versus 0.3).…”
Section: Discussionmentioning
confidence: 80%
“…In 2 additional animals where we acquired additional R 2 maps (data not shown), the data did suggest an increase in R 2 in IM after iodixanol; however, the magnitude of change was relatively small (approximately 10 s –1 ) compared with the observed R 2* change (approximately 100 s –1 ). Because it was also previously shown that L-NAME could reduce urine output, 41 it may explain why the R 2* was lower in the CIAKI-susceptible group after iodixanol. Although ioxalgate did show statistically significant increase in R 2* in IM, the values were comparable with the defined threshold (estimated slope of 0.32 versus 0.3).…”
Section: Discussionmentioning
confidence: 80%
“…In this sense, numerous studies demonstrated high expression levels of the neuronal isoform of nitric oxide synthase (nNOS) in both OT and VP neurons (31, 42) which similar to our findings with HO-1, is upregulated in an activity-dependent manner during osmotic challenges (43, 44). Differently from the HO/CO system however, the general consensus is that NO is constitutively produced within the SON and PVN, acting as a strong inhibitor of neuronal activity (31, 45, 46), and hormone release from the posterior pituitary (24, 25, 47, 48). Taken together, these studies support the notion that NO and CO are two functionally relevant gas molecules with opposing actions in the magnocellular system (i.e., NO inhibitory and CO excitatory).…”
Section: Discussionmentioning
confidence: 99%
“…Gas neurotransmitters, particularly nitric oxide (NO), have been shown to play important roles in neuroendocrine regulation (24)(25)(26). In the present study, we aimed to determine whether CO, another functionally relevant gas molecule in the brain (1,2), plays a role in the modulation of magnocellular neurosecretory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Ang II is best known for its role in the regulation of blood pressure, fluid balance and neuroendocrine function (11)(12)(13). It was recently demonstrated that Ang II primarily activated circumventricular neurons, leading to the activation of neurons in other forebrain regions (14), indicating that Ang II may exert multiple effects on neuronal activity.…”
Section: Introductionmentioning
confidence: 99%